PENEGAKAN HUKUM PIDANA TERHADAP KASUS KEBAKARAN HUTAN DAN LAHAN BERDASARKAN UNDANG-UNDANG NO. 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP PADA TAHAP PENYIDIKAN DI KOTA PONTIANAK - FEDRICK ROBEN HARDT NAINGGOLAN NIM. A1011161076 (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractCases of forest and land fires in Indonesia continue to occur every year, this shows that efforts to control forest and land fires in Indonesia have not been fully maximized. Various laws and regulations were issued by the government as a form of solving the problem of forest and land fires. Forest and land fires can be caused by natural factors and/or human activities. In Pontianak City, the issue of forest and land fires is also on the agenda for discussion every year. Apart from the dry weather factor, the lack of public or corporate legal awareness of the dangers of clearing land by burning is also a supporting factor for this case to occur every year. The presence of Law Number 32 of 2009 concerning Environmental Protection and Management as an answer to the problem of law enforcement against perpetrators of forest and/or land burning.Formulation of the problem Based on the explanation on the background, the writer can formulate the problem as follows: